Cervical incompetence - Valdivia Ponce, Eduardo (2015)
From the anatomical point of view a cervix is incompetent when its inner ring is abnormally dilated causing a broadened level of corpo-cervical junction channel. From the point of view obstetrician, it is considered that a cervix is incompetent when it allows a painless dilation to a degree sufficient to allow the membrabas herniation with consequent breakage and abortion before the end of the 36th. week of pregnancy.